Optimalisasi Kurikulum Muatan Lokal Keagamaan untuk Meningkatkan Kualitas Pembelajaran PAI di Sekolah Umum - Binti Masrufa (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This study aims to analyse the optimisation efforts of local religious content curricula to improve the quality of Islamic Education learning at SMPN 1 Mojowarno Jombang. The research was conducted using a qualitative approach and descriptive design. Data were collected through observation, interviews, and document review. The results showed that schools had implemented local religious content in the form of Arabic and Javanese language subjects. However, its implementation still faces several challenges, such as time allocation, teacher competence, availability of teaching materials, completeness of infrastructure, and cooperation with stakeholders. Therefore, optimization must be done through increasing time allocation, teacher training, developing teaching materials, strengthening infrastructure, cooperation with related stakeholders, and regular monitoring and evaluation. With such optimisation, it is hoped that implementing local religious content can run effectively and contribute maximally to improving the quality of Islamic Education learning and internalising religious values in students. Theoretically, the results of this study have contributed to developing an Islamic Education curriculum contextual to local needs.